Body Dissatisfaction and Eating Disorder Symptoms in Iranian Women Aspiring Fashion: The Mediating Role of Anxiety - Mandana Niknam; Niusha Nikjou; Payman Aminayi (مطالعات روانشناختی)
The aim of this study was to determine the relationship between body dissatisfaction and symptoms of eating disorders in aspiring fashion model women with the mediating role of anxiety. The present research was descriptive-correlation type. The research population included all women who were aspiring fashion models aged 20 to 40 in Tehran in 2023, a sample of 210 of whom were purposefully selected from beauty service centers and clinics, clothing mezons and gyms in Tehran. To collect data, body dissatisfaction questionnaires by Cooper et al., Beck's anxiety and eating disorder symptoms by Garner et al. were used. Pearson correlation test and structural equation modeling technique were used to analyze the data. The results indicated that anxiety mediated the relationship between body dissatisfaction and eating disorder symptoms in women aspiring to model. Additionally, all direct effects in the model were significant, demonstrating that body dissatisfaction influences anxiety, anxiety affects eating disorder symptoms, and body dissatisfaction directly impacts on eating disorder symptoms in this population. Therefore, by understanding the role of body dissatisfaction and anxiety in developing eating disorder symptoms and the related problems, Psychologists can take practical actions and appropriate interventions.